An Analysis of Students’ Speaking Anxiety at 7th Grade of Almumtaz Boarding School - Syafitri, Poppy Fauziah; Roza, Veni; Reflinda, Reflinda; Syafitri, Widya (Lembaga Yasin AlSys, 2023)
This research was conducted due to several problems in speaking activity in the classroom, problems refer to the students’ feelings of anxiety to speak in the learning process. Based on the preliminary research, the researcher found that the students were anxious to speak in the classroom for some reasons like low of speaking aspects mastery and low of self-cofidence. In foreign language learning, students’ speaking ability can be affected by psychological factors. Thus, this research aimed to find out the factors that cause students’ speaking anxiety. This research was done in Al-Mumtaz Boarding School. The design of this research was descriptive qualitative research. In order to collect the data, the researcher used non-participative observation and semi-structured interview as the instruments. The population of this research was all the seventh grade students of Al-Mumtaz Boarding School which consists of four classes, one boy’s class and three girls’ classes. The researcher used purposive sampling to get the sample for the observation because all the populations had same characteristics. The observation’s sample consist of two classes, one boy’s class and one girl’s class. Then, the researcher used snowball sampling to get the sample for the interview. There were fourteen students who were interviewed in this research. The result showed that there were several factors that cause students’ speaking anxiety at seventh grade of Al-Mumtaz Boarding school, either on boy’s class or girl’s class. Those factors are fear of negative responses from the others, low of self-confidence, fear of making mistakes and low of speaking aspects mastery (pronounciation, comprehension and vocabulary). In conclusion, there were four factors that cause students’ speaking anxiety at seventh grade of Al-Mumtaz Boarding School.